Acenaphthene-triphenylamine (acceptor–donor) based luminophores for organic light emitting diodes: combined experimental and theoretical study. Issue 1 (10th November 2021) - Tagare, Jairam; Kajjam, Aravind Babu; Singh, Kasturi; Patel, Sabita; Vaidyanathan, Sivakumar
Abstract : A series of acenaphthene derivatives were designed and synthesized by incorporating acenaphthene-imidazole as an electron-transporting moiety and triphenylamine (TPA) as a hole-transporting moieties. All the dyes showed a broad bluish-white to yellowish-orange emission with emission maxima in the range of 520–600 nm. Abstract : In this work, a series of acenaphthene derivatives (AC-derivatives) were designed and synthesized by incorporating imidazole as an electron deficient moiety and triphenylamine (TPA) as an electron rich moiety with different functional groups at the N1 position of imidazole. All the dyes were structurally characterized by spectroscopic methods ( 1 H NMR, 13 C NMR, IR, and Mass) and some of the dyes were characterized by single crystal X-ray diffraction. The detailed thermal, photophysical and electrochemical properties were systematically investigated. All the dyes showed good thermal stability with high thermal decomposition ( T d ) temperatures ranging from 400 to 430 °C. All the dyes had similar absorption behaviour, with peak wavelengths at 240 nm and 350 nm assigned to the π → π* transitions of the aromatic segments. All the dyes exhibited a broad bluish-white to yellowish-orange emission with the emission maximum in the range of 520–600 nm. Electrochemical analysis was performed to discover the HOMO and LUMO energy levels of the dyes, which were verified using DFT calculations. Theoretical investigations, such as optimization, singlet–triplet and HOMO and LUMO energy levels calculations, were calculated using DFT and TD-DFT analysis. The excited singlet–triplet energy gaps of the dyes were estimated and correlated to the structural and energetic characteristics of the known host materials. In addition, examinations were carried out to find the optical, electronic, charge transport and stability properties of dyes for use as emissive and charge transport materials in organic light emitting devices (OLEDs). All the dyes are good emissive materials with their hole transporting nature more favourable than the electron transporting nature. The theoretical investigations clearly indicate that AC-mCF3 has more potential as an emitter for OLED applications.